Hubungan Perilaku Konsumsi Makanan Cepat Saji terhadap Tingkat Keparahan Akne Vulgaris pada Mahasiswa Laki-Laki: Hasil Penelitian - Mariani Santosa; Cindy Anastasia; Lonah; Yuliana; Erwin Yantho; Ecie Budiyanti (Cermin Dunia Kedokteran, 2025)
Introduction: Acne vulgaris has the highest prevalent skin disease in the world, with food is one of the most common triggers in adolescents. Availability of fast food has influenced young adults eating pattern. This study aims to determine the relationship between frequency of fast food consumption and severity of acne vulgaris in male students. Methods: This cross-sectional study was conducted on 129 male students. Frequency of fast food consumption and severity of acne vulgaris was measured using a modified FFQ questionnaire and GAGS score. Data were processed with STATA and analyzed using Chi-square. Results: The result showed that 65.89% male students often consumed fast food and the majority of respondents experienced mild acne vulgaris (55.81%). There was a significant relationship between frequency of fast food consumption and severity of acne vulgaris (p=0.020). Conclusion: The results of this study suggest a significant relationship between frequency of fast food consumption and severity of acne vulgaris among male students.